Comparative proteomic characterization of bovine milk containing β‐casein variants A1A1 and A2A2, and their heterozygote A1A2. (25th August 2020) - Wang, Xiaxia; Yu, Zhongna; Zhao, Xiaowei; Han, Rongwei; Huang, Dongwei; Yang, Yongxin; Cheng, Guanglong
Abstract: BACKGROUND: Genetic variants of β ‐casein are cosnidered to affect the components of milk. However, limited data are available on the bovine protein components correlated with β ‐casein variants at the proteome level. In the present study, cows producing milk containing β ‐casein variants (A1A1 and A2A2) and their heterozygote (A1A2) were identified using a high‐resolution melting method, and milk samples were collected and tested. Comparative analyses of casein micelles, whey and milk fat globule membrane fractions in each milk variant were performed using a label‐free proteomics approach. RESULTS: The results obtained showed that ceruloplasmin and cathelicidin‐2 were the most abundant proteins in milk containing variant A1A1; lactoferrin and CD5 molecule‐like were the most abundant proteins in milk containing variant A2A2; and selenoprotein P and osteopontin were the most abundant proteins in milk containing heterozygote A1A2. Differences in protein components in milk containing the different β ‐casein variants were visualized using hierarchical clustering, and profiles were separated using principal components analysis. The differentially expressed proteins in milk containing A1A1, A2A2 or A1A2 were predominantly involved in response to stress and defense response according to their Gene Ontology annotations. CONCLUSION: Our findings provide new insights into differentially expressed milk proteins corresponding to the presence of different β ‐casein variants. This knowledge will help determine their potential biological functions in dairy products and the effects on human health. © 2020 Society of Chemical Industry